Design of a waiter robot and automatic cleaning and disinfection table (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
With the industrialization of communities, restaurants are using new mechanisms from ordering to serving food, which leads to better performance, faster and easier service, less staff, and reduced costs, and other benefits. One of the mechanisms that have recently become very popular is the use of robots as waiters in the restaurant industry. In addition, these robots play an important role in an era when people should not be gathered in one environment due to the spread of the coronavirus. In fact, the purpose of designing such robots is to reduce manpower and minimize human contact to prevent the spread of the Coronavirus.In this project, in addition to designing a waiter robot, an automatic table has been designed that intelligently collects garbage and sprays alcohol on the table to prevent the spread of Coronavirus.